Deflection and cracking behavior of SFRSCC beams reinforced with hybrid prestressed GFRP and steel reinforcements - Mazaheripour, Hadi (2016)
In the present work, the deflection and cracking behavior of I-shaped cross-sectional beams of Steel Fiber Reinforced Self-Compacting Concrete (SFRSCC) reinforced in flexure with hybrid prestressed steel strand and glass fiber reinforced polymer (GFRP) bars was investigated. Combining prestressed GFRP bars of relatively low elasticity modulus, but immune to corrosion (located with a small concrete cover), with prestressed steel strand (with higher concrete cover to avoid corrosion), a good balance in terms of reinforcement effectiveness, ductility, durability and cost competitiveness can be obtained. The steel strand aims also to assure the necessary flexural strengthening of the beams if GFRP bars become ineffective in case of fire occurrence. This work presents and discusses the results obtained from the experimental study of the beams tested in flexure under monotonic loading conditions. Additionally, the predictive performance of the available formulation in the design codes for the case of Fiber Reinforced Concrete (FRC) and FRP reinforced Concrete (FRP-RC) was assessed to be used for the proposed hybrid system.